2013
DOI: 10.1093/cvr/cvt094
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AP-1 signaling by JDP2 overexpression protects cardiomyocytes against hypertrophy and apoptosis induction

Abstract: A central role of AP-1 in the induction of hypertrophy and apoptosis in cardiomyocytes is demonstrated. Besides these protective effects of AP-1 inhibition on factors of cardiac remodelling, AP-1-inhibition impairs contractile function. Therefore, AP-1 acts as a double-edged sword that mediates mal-adaptive cardiac remodelling, but is required for maintaining a proper contractile function of cardiomyocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…That AP‐1 is a mediator of hypertrophy and apoptosis in β‐adrenoceptor stimulated cardiomyocytes has been shown by use of transgenic mice overexpressing the AP‐1 inhibitor jun dimerization protein 2 (JDP2). JDP2 overexpression prevented isoprenaline (ISO)‐induced hypertrophy as well as TGFβ‐induced apoptosis in cardiomyocytes (Hill et al ., ). But AP‐1 is also required to preserve the contractile function of cardiomyocytes because AP‐1 inhibition by JDP2 overexpression attenuated contractile responses induced by β‐adrenoceptor stimulation (Hill et al ., ).…”
Section: The Tak1 Pathway Is Pro‐hypertrophic and Prevents Cell Deathmentioning
confidence: 97%
“…That AP‐1 is a mediator of hypertrophy and apoptosis in β‐adrenoceptor stimulated cardiomyocytes has been shown by use of transgenic mice overexpressing the AP‐1 inhibitor jun dimerization protein 2 (JDP2). JDP2 overexpression prevented isoprenaline (ISO)‐induced hypertrophy as well as TGFβ‐induced apoptosis in cardiomyocytes (Hill et al ., ). But AP‐1 is also required to preserve the contractile function of cardiomyocytes because AP‐1 inhibition by JDP2 overexpression attenuated contractile responses induced by β‐adrenoceptor stimulation (Hill et al ., ).…”
Section: The Tak1 Pathway Is Pro‐hypertrophic and Prevents Cell Deathmentioning
confidence: 97%
“…Moreover, according to previous studies, the expression of AP‐1 is increased by the JAK2/STAT3 pathway, which is associated with inflammation and cardiac hypertrophy. However, according to Hill et al study, the expression of AP‐1 is necessary for cardiac contractile function, and nonexpression of it is associated with contractile dysfunction in cardiac cells (Hill et al, ). Furthermore, the mentioned study showed that the activation of JAK2/STAT3 resulted in the prevention of apoptosis by HSF1.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…56,63 Replicating variations of in vivo phenotypes, the size, contractility, and electrophysiology of neoCMs in culture are known to vary during the first 7 d after isolation. 5355 When compared to rat neoCMs, the variation of in vitro physiological phenotypes of mouse neoCMs is less dependent on serum growth factors, 54 involving an increase with time in the contractility rate, 64 contraction velocities, 65 and a decrease of times of contraction. 65 Such changes are not observed with our microsposts treated with Plasma and GPTMS laminin .…”
Section: Discussionmentioning
confidence: 99%
“…5355 When compared to rat neoCMs, the variation of in vitro physiological phenotypes of mouse neoCMs is less dependent on serum growth factors, 54 involving an increase with time in the contractility rate, 64 contraction velocities, 65 and a decrease of times of contraction. 65 Such changes are not observed with our microsposts treated with Plasma and GPTMS laminin . The higher stability of APTES glut-laminin -mediated cell anchorage increases the efficiency of force transfer to posts in the long term, which may lead to the occurrence of in vivo contractile phenotypes.…”
Section: Discussionmentioning
confidence: 99%